2018
DOI: 10.1177/2059204318757021
|View full text |Cite|
|
Sign up to set email alerts
|

Using agent-based models to understand the role of individuals in the song evolution of humpback whales (Megaptera novaeangliae)

Abstract: Male humpback whales produce hierarchically structured songs, primarily during the breeding season. These songs gradually change over the course of the breeding season, and are generally population specific. However, instances have been recorded of more rapid song changes where the song of a population can be replaced by the song of an adjacent population. The mechanisms that drive these changes are not currently understood, and difficulties in tracking individual whales over long migratory routes mean field s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 60 publications
1
30
0
Order By: Relevance
“…The new song variants in corn buntings show relatively limited change, making it more likely that change resulted from a learning or production error at the beginning of the season ( McGregor et al, 1997 ). A similar process may occur in humpback song; recent work using agent-based models of song evolution demonstrated that production errors ( rate = 1 or 0.1%) facilitated the gradual song evolution observed in the wild ( Mcloughlin et al, 2018 ). Using both novelty bias and production errors in the model mirrored the progressive song evolution observed in the South Pacific ( Mcloughlin et al, 2018 ).…”
Section: Song Change In Space and Time: Whales And Songbirdsmentioning
confidence: 88%
See 2 more Smart Citations
“…The new song variants in corn buntings show relatively limited change, making it more likely that change resulted from a learning or production error at the beginning of the season ( McGregor et al, 1997 ). A similar process may occur in humpback song; recent work using agent-based models of song evolution demonstrated that production errors ( rate = 1 or 0.1%) facilitated the gradual song evolution observed in the wild ( Mcloughlin et al, 2018 ). Using both novelty bias and production errors in the model mirrored the progressive song evolution observed in the South Pacific ( Mcloughlin et al, 2018 ).…”
Section: Song Change In Space and Time: Whales And Songbirdsmentioning
confidence: 88%
“…A similar process may occur in humpback song; recent work using agent-based models of song evolution demonstrated that production errors ( rate = 1 or 0.1%) facilitated the gradual song evolution observed in the wild ( Mcloughlin et al, 2018 ). Using both novelty bias and production errors in the model mirrored the progressive song evolution observed in the South Pacific ( Mcloughlin et al, 2018 ). However, no scenarios resulted in song revolutions; to produce a revolution in the agent-based model required a song memory to be added ( Lamoni, 2018 ).…”
Section: Song Change In Space and Time: Whales And Songbirdsmentioning
confidence: 88%
See 1 more Smart Citation
“…The ways in which they progressively morph phrases within and across songs does not match with what selectionist models of cultural evolution predict should happen, but neither do they match with a neutral model of evolutionary change in which random mutations spread through a population ( Kimura, 1979 ). Evolutionary models of collective changes appear to be inadequate for characterizing the ways in which singers modify their songs over time ( McLoughlin et al, 2018 ). Whether dynamic systems models of interacting agents can meet this challenge remains to be seen.…”
Section: Discussionmentioning
confidence: 99%
“…Although it is presumed that song transmission is facilitated by male interchange between populations on shared feeding grounds (Garland et al 2013;McLoughlin et al 2018) or via transfer along shared migratory routes (Noad et al 2000;Garland et al 2011), the specific function of song change, the significance underlying rapid versus progressive changes, and the contribution of individual inventiveness as opposed to "template" patterning has yet to be determined.…”
Section: Humpback Whale Communication 141 Humpback Whale Songmentioning
confidence: 99%